ANALISIS RISIKO PRODUKSI BUNGA KRISAN POTONG (CHRYSANTHEMUM) DI DESA SIDOMULYO KOTA BATU - Fadlilah, Siti Nur; Ariadi, Bambang Yudi; Relawati, Rahayu (University of Muhammadiyah Malang, 2019)
This study aims to analyze the income of cut chrysanthemum farming and the effect of the use of chrysanthemum cut production inputs on the risk of chrysanthemum production in Sidomulyo Village, Batu City. This research was carried out during May and June for one time planting at the last harvest in 2018 year. Data collection was obtained through interviews to 34 farmers that taken as a whole (census method). Farm income is analyzed using Economic Analysis while the factors that influence the risk of chrysanthemum production are cut analyzed using multiple linear regression analysis Cobb-Douglass production function model and Just and Pope production function. The results of the analysis show that Chrysanthemum farming income cut profitable and efficientc, seen from the results of the R / C Ratio amounting to 1,90. Production factors significantly affect the productivity of cut chrysanthemums is seeds, chemical fertilizers, and labor while the factors that significantly affect the risk of production is chemical fertilizers.